Holography in the Large J Limit of AdS/CFT Correspondence and Its Applications - Yoneya, Tamiaki (2006)
Prog.Theor.Phys.Suppl.164:82-102,2007 We give a brief expository discussion on the holographic correspondence of correlation functions in the large J limit of AdS/CFT conjecture. We first review our proposals on the interpretation of the so-called GKPW relation in the large J limit or BMN limit, which are based upon a tunneling picture in relating the AdS bulk to its boundary. Some concrete results, explicitly confirming our picture, are summarized. We then proceed to comment on various issues related to this subject, such as extension of the present picture to nonconformal Dp-brane backgrounds, the correlators of deformed Wilson loops, spinning-string/spin-chain correspondence, and the inclusion of higher string-loop effects. In particular, as for the deformation of Wilson loops, we present a typical tunneling world-sheet solution which can be used for direct derivation of the expectation values of deformed Wilson loops following our picture.